Sistem Monitoring Jumlah Pengunjung Ruang Rawat Inap Rumah Sakit Berbasis Android - Daputri Karmita; Dodon Yendri (CHIPSET, 2022)
A Hospital is a health facility that aims to provide good health services for patients. The physical environment of the inpatient room also affects the patient's psychological condition. The inpatient room should raise optimism so that it can help the patient's healing process. Standard operating procedures in a hospital limit the number of visitors in each inpatient room. This is especially true in the class 1 inpatient room, where the number of patients is limited to two people and the maximum number of visitors limited to 2 people. However, even though the number of visitors to the hospital has been determined, many of the patients' families or relatives who want to visit violate these rules. This happens even though it has been prohibited or without the knowledge of the hospital staff. This paper describes the development of an Android based system to monitor the number of visitors to the hospital's inpatient room, streamlining the number of visitors to the hospital's inpatient room. The researcher uses a camera so that he can immediately capture the number of visitors in the room. The captured picture are processed in a Raspberry pi to count the number of visitors in the room, using tensorflow as an object detector (visitor). The system can then send notifications to the application when the number of visitors exceeds the safe limit. Researchers also use a mobile application to display monitoring results. so that with this system, the head of the hospital room and the hospital security guard can find out the number of visitors who are in the hospital inpatient room and the number of visitors who exceed the maximum limit.